2019
DOI: 10.1029/2018jf004705
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lithospheric Flexure in the Landscape Evolution of the Wilkes Subglacial Basin and Transantarctic Mountains, East Antarctica

Abstract: Reconstructions of the bedrock topography of Antarctica since the Eocene‐Oligocene Boundary (approximately 34 Ma) provide important constraints for modeling Antarctic ice sheet evolution. This is particularly important in regions where the bedrock lies below sea level, since in these sectors the overlying ice sheet is thought to be most susceptible to past and future change. Here we use 3‐D flexural modeling to reconstruct the evolution of the topography of the Wilkes Subglacial Basin (WSB) and Transantarctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 78 publications
(202 reference statements)
1
27
0
Order By: Relevance
“…A similar setting may be envisaged in particular for the back‐arc regions of the Ross Orogen that may in parts underlie the Wilkes Subglacial Basin (e.g., Ferraccioli, Armadillo, Jordan, et al, ; Jordan et al, ). However, there are complicating effects in EANT, due to the much more recent Cenozoic uplift of the TAM (at the former site of the Ross Orogen) and the associated lithospheric flexure of the craton and its margin beneath the Wilkes Subglacial Basin (e.g., Paxman et al, , , and references therein). Irrespectively, however, we also note that some potentially conjugate Precambrian terranes in Australia that lie along the eastern edge of the Gawler Craton appear to have anomalously thick crust, most notably the seismically defined Numil terrane that has crust up to 45 km thick close to a proposed major suture zone of inferred Paleoproterozoic or even older Archaean age (Betts et al, ; Curtis & Thiel, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar setting may be envisaged in particular for the back‐arc regions of the Ross Orogen that may in parts underlie the Wilkes Subglacial Basin (e.g., Ferraccioli, Armadillo, Jordan, et al, ; Jordan et al, ). However, there are complicating effects in EANT, due to the much more recent Cenozoic uplift of the TAM (at the former site of the Ross Orogen) and the associated lithospheric flexure of the craton and its margin beneath the Wilkes Subglacial Basin (e.g., Paxman et al, , , and references therein). Irrespectively, however, we also note that some potentially conjugate Precambrian terranes in Australia that lie along the eastern edge of the Gawler Craton appear to have anomalously thick crust, most notably the seismically defined Numil terrane that has crust up to 45 km thick close to a proposed major suture zone of inferred Paleoproterozoic or even older Archaean age (Betts et al, ; Curtis & Thiel, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moho depth estimates from seismological studies differ for the same station by up to 10 km, even along a relatively well‐studied profile (Figure ). The profile stretches from the TAM to the GSM (Creyts et al, ; Paxman et al, ) crossing the southern Wilkes Subglacial Basin (Ferraccioli et al, ; Ferraccioli, Armadillo, Jordan, et al, ; Ferraccioli & Bozzo, ; Jordan et al, ; Paxman et al, , ; Studinger et al, ). Seismic data have been acquired by deployments from the TAMSEIS (Hansen et al, ; Lawrence et al, , ) and the GAMSEIS (Kanao et al, ) experiments.…”
Section: ‐D Lithospheric Cross‐sectionsmentioning
confidence: 99%
“…Short-wavelength residuals could originate from imperfect topographic or ice correction models onshore or sediment models in offshore areas. It is also possible that they represent topographic masses that are not in local isostatic balance but compensated regionally due to lithospheric flexure (e.g., Paxman et al, 2019). However, the RMS misfit of~380 m is still small compared to the corresponding crustal thickness variation that would be needed to compensate such a topographic load.…”
Section: 1029/2019jb017997mentioning
confidence: 99%
“…In contrast, the broad and low‐elevation morphology of basins in the central Australo‐Antarctic domain allowed for the development of larger fluvial braided systems and river deltas (Paxman, Jamieson, Ferraccioli, et al, 2019; Sauermilch et al, 2019), which provided a substantial amount of detrital material to the Gondwana breakup passive margin basins (Sauermilch et al, 2019). The expansion of the East Antarctic Ice Sheet since the Eocene exacerbated these conditions with high erosion rates (~100 m Ma −1 ) in the Lambert Rift (Thomson et al, 2013) and dynamic erosion from a marine‐based ice sheet in the Aurora (Young et al, 2011) and Wilkes Subglacial Basin (Paxman et al, 2018; Paxman, Jamieson, Ferraccioli, et al, 2019). Together, these observations suggest that tectonic‐controlled relief has exerted a key influence on long‐term denudation rates and the evolution of the subglacial landscape of East Antarctica, providing a unique example of a continental interior where long‐term erosion and associated dynamic responses (i.e., flexure) over millions of years acted to reinforce preexisting topographic relief.…”
Section: Discussionmentioning
confidence: 99%
“…Colored circles show published bedrock AFT and AHe data from the Lambert Rift area (Arne, 1994; Lisker et al, 2003; Lisker, Gibson, et al, 2007), Vestfold Hills (Lisker, Wilson, & Gibson, 2007), and Terre Adélie/George V Land (Lisker & Olesch, 2003; Rolland et al, 2019) as well as reconnaissance AFT data of Arne et al (1993). Sedimentary basin‐bounding faults in the EARS (Ferraccioli et al, 2011), Knox Rift (Maritati et al, 2016), Aurora and Vincennes Subglacial Basins, (Aitken, Roberts, et al, 2016), Wilkes Subglacial Basin (Paxman, Jamieson, Ferraccioli, et al, 2019, and references therein) are highlighted in red; dashed black lines correspond to the inferred path the Mirny Fault (Daczko et al, 2018) and Gamburtsev Suture (Ferraccioli et al, 2011), which together represent the paleoplate boundary between Indo‐Antarctica and Australo‐Antarctica (Mulder et al, 2019); dashed box in panel (a) indicates a detail of the Bunger Hills region shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%